Análise do potencial da bicicleta para a distribuição urbana de mercadorias - Carla de Oliveira Leite Nascimento (2019)
Urban distribution of goods plays an important role in the performance of a region. However, urban cargo also causes disruption to the city life Therefore, one way to minimize the impacts of urban freight transport is to propose sustainable modes of delivery. In this context, it is noteworthy that the use of bicycles in urban freight transport (modality called cyclelogistics) has been discussed as an interesting possibility of configuring a sustainable mode for urban freight transport. This dissertation proposes to analyse the factors that influence the use of bicycles for urban distribution of goods. To achieve this objective, two approaches were used, the first involving existing cyclelogistics companies from Brazil. With these companies, we sought to understand how the system works, highlighting the advantages and difficulties faced in order to identify which are the factors that influence the operation of these companies and those that are impeding the growth of this type of delivery in Brazil. It was identified that topography, theft and infrastructure are the variables that affect delivery operations by bicycle. In the second approach, the variables that influence the decision of logistics operators in the use of bicycles for the urban distribution of goods were identified. The theory of planned behaviour (TCP) together with the statistical technique of logistic regression was adopted to define these variables. As a result, the variables "system efficiency and reliability", “environmental awareness", "available infrastructure", “companies and society's behaviour regarding bicycle adoption” were those that obtained statistical significance in this influence and that interfere positively in the intention of implementing the bicycle.